2021
DOI: 10.1016/j.acra.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Induced Lymphadenopathy in a Specialized Breast Imaging Clinic in Israel: Analysis of 163 cases

Abstract: Introduction: Following vaccination of Israeli population with Pfizer-BioNTech COVID-19 Vaccine, an unusual increase in axillary-lymphadenopathy was noted. This study assesses the rate and magnitude of this trend from breast-imaging standpoint. Materials and Methods: Participants undergoing breast-imaging, in whom isolated axillary-lymphadenopathy was detected were questioned regarding SARS-CoV-2 vaccine to the ipsilateral arm. Patients’ and imaging characteristics were stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 20 publications
3
42
0
Order By: Relevance
“…The majority of axillary lymphadenopathy (96%) in the current study was subclinical and detected by ultrasound. This was consistent with the results of another study wherein 97.5% of lymphadenopathy in 163 cases in a breast imaging clinic were only detected by imaging such as ultrasound, magnetic resonance imaging, or mammography [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of axillary lymphadenopathy (96%) in the current study was subclinical and detected by ultrasound. This was consistent with the results of another study wherein 97.5% of lymphadenopathy in 163 cases in a breast imaging clinic were only detected by imaging such as ultrasound, magnetic resonance imaging, or mammography [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
“…In conjunction with the massive administration of coronavirus disease 2019 (COVID-19) vaccines, we observed an unusual increase in the number of imaging-detected unilateral axillary lymphadenopathy cases at our breast imaging clinic. Vaccine-associated lymphadenopathy has also been recently reported as a frequent imaging finding after COVID-19 vaccination [ 1 , 2 , 3 ]. In clinical trials of the Moderna vaccine, axillary swelling or tenderness was reported in 11.6% and 16.0% of patients following the first and the second dose, retrospectively.…”
Section: Introductionmentioning
confidence: 99%
“…As she was asymptomatic, had her screening mammogram not been performed or significantly delayed, her breast cancer would have not been detected, likely resulting in increased morbidity or mortality due to a delay in diagnosis. Additionally, presence of reactive lymphadenopathy does not exclude the possibility of malignancy 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Women who have received either the Pfizer or Moderna COVID-19 vaccine have presented with unilateral axillary lymphadenopathy after both the first and second doses of these vaccines. A previous review study noted that this occurred most commonly in between 1-4 weeks post vaccination, and is usually subclinical in nature 3 , 4 . If the lymphadenopathy is due to an immune response from the vaccine, and not malignancy, this represents additional cost for the follow up diagnostic studies as well as undue psychological distress for the patient 5 .…”
Section: Introductionmentioning
confidence: 98%
“…The changes in lymph node features after vaccination, reported in a study of 91 volunteer employees, include an increase in the lymph node size by 5.3 mm, increase in cortical thickness by 2.1 mm, increase in the number of visible lymph nodes by 1.8, and an overall increase in the associated Doppler signal [3] . Faermann et al reported that the mean cortical thickness of lymph nodes after vaccination was 5 mm ± 2 mm and that the longitudinal length of lymph nodes increased between the first and the second doses of a mRNA COVID-19 vaccine [4] . As reports of vaccine-induced reactive adenopathy increased, management recommendations were developed and modified regarding the need for imaging and biopsy [5] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%